Informal Whānau/Kinship caregivers experiences of community support - Christie McGiven; Christa Fouché (Kōtuitui, 2025)
Informal Whānau/Kinship Caregivers navigate the complexities of parenting children not born to them, manage complex family relationships and often do so with limited resources available. Research related to this specific group of caregivers is lacking within New Zealand. This article offers an overview of key insights taken from a small, narrative study of the community support experiences of six New Zealand Informal Whānau/Kinship Caregivers, collected across 12 interviews. Key themes were constructed from their collective stories and three of the prominent themes related to community support experiences are presented in this article, namely: (a) leading service coordination; (b) accessing a range of support options; and (c) developing trust-based relationships. The application of Ecological Systems Theory is used to discuss the role of Care Sector Organisations in supporting Informal Whānau/Kinship Caregivers to meet the needs of their children. This article highlights the importance of resourcing, not only Informal Whānau/Kinship Caregivers, but the community-based support services and professionals seeking to assist them.